An Ecological Approach in Designing Rosella Agrotourism in Kediri Regency - Michel Dio Susanto; Y.A Widriyakara Setiadi; Heristama Anugerah Putra (Universitas Bandar Lampung (UBL), 2022)
Agrotourism is one of the efforts in preserving biodiversity and can be used as nature tourism. For local farmers, they hope to be able to develop cultivation of this rosella plant which is packaged in the form of agro-tourism. Where rosella is the main crop and commodity that grows and can be a source of income for farmers around this area. Agrotourism can also be useful as a means of education, the processed product of rosella itself is a very popular product in Kediri. This research uses Archer's three-phase method with analytical, creative, and executive phases. Rosella agro-tourism design applies an ecological approach as an effort to preserve nature. In addition, another goal in designing rosella agro-tourism design with an ecological approach can maintain most of the existing land and natural resources. So that agrotourism is able to increase the number of tourists and preserve nature in Kediri Regency, as well as become a means of education. So that this agro-tourism can become the center of a new tourist destination in Kediri Regency, become a tourism that is in harmony and friendly with the surrounding environment, and can improve the creative economy of the surrounding community.